Digital law: The pursuit of certainty - M I. Inozemtsev (Цифровое право)
The article deals with the development o digital law as an instrument for regulating the digital economy. It is proved that, within the academic environment, the concept of “Internet law” is still more well-established than the concept of “digital law”. It is in this manner that the legal sphere responds to the challenges of the digital revolution and reflects the digital economy. The debate as to whether “Internet law” can be considered either as a separate branch of law or as a branch of legislation has not yet subsided. Nevertheless, “Internet law” is undoubtedly an independent academic discipline, textbooks on which are published in Russia. However, Russia needs to develop a digital economy; this is why the national project “Digital Economy of the Russian Federation” was adopted in 2018, regulatory support for which forms the basis of digital law in Russia. At the same time, the extensive experience of digital economy regulation in both its neighbouring countries and beyond is taken into account. Especially attractive is the national strategic model, which assumes the most rapid procedure for adopting changes and consequently adapting digital legislation, is aimed at the long-term perspective, and lets popular opinion — as well as the opinions of public organizations, the business community, and government representatives — be taken into account. In addition to foreign experience in regulating the digital economy, we should also use the best practices of domestic and foreign legal science.